Antithrombotic Action of Endogenous Porcine Protein C Activated with a Latent Porcine Thrombin Preparation - McBane, Robert D; Wysokinski, Waldemar E; Chesebro, James H; Owen, Whyte G (Thrombosis and Haemostasis, 1995)
Endogenously activated protein C is evaluated for antithrombotic activity in porcine carotid arteries subjected to mechanical trauma. Protein C is activated by intravenous administration of guanidinobenzoyl- thrombin, which binds to thrombomodulin and there deacylates to yield thrombin. The bound, transiently active thrombin yields a peak of anticoagulant activity between 5 and 10 min after infusion of the latent thrombin. Inhibition of thrombin binding in vivo by co-infusing an active-site-blocked thrombin preparation elicits acute and lethal systemic thrombosis. Nearly occlusive platelet thrombosis, which occurs within 30 min of crushing 1 cm segments of carotid arteries with a standard hemostat, is blocked by endogenous protein C activation initiated 2 min before the crush injury. It is concluded that activated protein C blocks thrombosis in deeply injured musculo-elastic arteries, and that activation of latent thrombin bound to thrombomodulin in vivo is a practical means for delivery of pharmacologically effective concentrations of activated protein C.